CCIE security practice labs - Bhaiji, Fahim Hussain Yusuf (CCIE self-study., 2004)
"CCIE Security Practice Labs provides a series of complete practice labs that mirror the difficult hands-on lab exam. Written by a CCIE Security engineer and Cisco Systems CCIE proctor, this book lays out seven end-to-end scenarios that are both complex and realistic, providing you with the practice needed to prepare for your lab examination and develop critical-thinking skills that are essential for resolving complex, real-world security problems. While many engineers are able to configure single technologies in standalone environments, most will struggle when dealing with integrated technologies in heterogeneous environments." "CCIE Security Practice Labs consists of seven full-blown labs. The book does not waste time covering conceptual knowledge found in other security manuals, but focuses exclusively on these complex scenarios. The structure of each chapter is the same, covering a broad range of security topics. Each chapter starts with an overview, equipment list, and general guidelines and instructions on setting up the lab topology, including cabling instructions, and concludes with verification, hints, and troubleshooting tips, which highlight show and debug commands. The companion CD-ROM contains solutions for all of the labs, including configurations and common show command output from all the devices in the topology."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved